Polyamide coated filter membrane, filters, and methods

The coated filter membrane, featuring a porous polymer filter layer coated with a crosslinked polyamide film, addresses the challenges of metal extraction and solvent limitations in traditional nylon filters, achieving effective contaminant removal and high purity in acidic liquids.

JP2025060678AActive Publication Date: 2025-04-10ENTEGRIS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024217228
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-04-30
Filing Date
2024-12-12
Publication Date
2025-04-10
Estimated Expiration
2039-04-10

AI Technical Summary

Technical Problem

Existing filter membranes, particularly those made from nylon, face challenges when exposed to acidic liquids, as metal catalysts can be extracted, leading to contamination, and these membranes are not soluble in a wide range of solvents, limiting their application in microelectronic device processing.

Method used

A coated filter membrane is developed, comprising a porous polymer filter layer coated with a non-porous crosslinked polyamide film. This coating is applied using a solvent like propanol, which is non-acidic and non-ionic, avoiding the use of formic acid or calcium chloride, and is crosslinked to enhance solvent resistance.

Benefits of technology

The coated filter membrane effectively removes contaminants and impurities from acidic liquids, maintaining high purity levels and stability, thus addressing the limitations of traditional nylon filters in microelectronic device processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060678000001_ABST
    Figure 2025060678000001_ABST
Patent Text Reader

Abstract

To provide a novel and improved filter in the field of microelectronics device processing.SOLUTION: A coated filter membrane comprises: a porous polymeric filter layer comprising a polyolefin; and a crosslinked polyamide film at least partially coating the surface of the porous filter layer, wherein the coated filter membrane has a bubble point in a range from 2 to 400 psi, measured using HFE 7200, at a temperature of 20-25°C.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The following description relates to filter membranes that include a porous polymeric filter layer coated with a layer that contains a crosslinked polyamide polymer; methods of making the coated filter membranes, filter components and filters; and methods of using the coated filter membranes, filter components and filters to filter fluids, such as liquid chemicals, and remove unwanted substances from the fluids. [Background technology]

[0002] Filter membranes and filter products used to remove unwanted materials from useful fluid streams are essential tools of modern industry. Useful fluids that are treated using filters include water, liquid industrial solvents and process fluids, industrial gases used in manufacturing or processing (e.g., in semiconductor fabrication), and liquids having medical or pharmaceutical uses. Unwanted materials removed from fluids include impurities and contaminants such as particles, microorganisms, and dissolved chemical species. Specific examples of filter applications include use in the pharmaceutical industry to remove particles and bacteria from therapeutic fluids, for use in microelectronics and semiconductor processing, and for treating ultra-high purity aqueous and organic solvent solutions for water purification processes.

[0003] To perform the filtering function, the filter product includes a filter membrane responsible for removing unwanted substances. The filter membrane may be in the form of a flat sheet that may be wound (e.g., spirally), pleated, etc., as required. Alternatively, the filter membrane may be in the form of a hollow fiber. The filter membrane may be contained in a housing such that the fluid to be filtered enters the inlet of the filter and must pass through the filter membrane before passing through the outlet of the filter.

[0004] Filter membranes may be constructed from porous structures with an average pore size that can be selected based on the application of the filter, i.e., the type of filtration performed by the filter. Typical pore sizes are in the micron or submicron range, such as from about 0.001 micron to about 10 microns. Membranes with an average pore size of about 0.001 to about 0.05 microns are generally classified as ultrafiltration membranes. Membranes with pore sizes between about 0.05 to 10 microns are generally classified as microporous membranes.

[0005] Porous polymeric films, including those made from various fluoropolymers, polyolefins, and nylon materials such as nylon 6 and nylon 66, are a common type of filter membrane. Nylon filters are used commercially to filter solvent materials for photolithography processes for semiconductor fabrication. These processes require solvents with extremely high levels of purity and therefore must be filtered using extremely efficient filtration systems. Filters made from nylons with controlled small pore sizes can be prepared that may be effective for these applications. However, the liquids used in microelectronics and semiconductor processing can be acidic. Additionally, some nylons are polymerized using metal catalysts such as magnesium. When such nylon types of filter membranes are exposed to acidic liquids, metals (e.g., magnesium) are susceptible to extraction from the nylon into the acidic fluid being filtered, where the metal is considered a contaminant. Additionally, nylons designed to be inert and solvent resistant are not necessarily soluble in a wide selection of solvents. This results in fewer options for preparing nylon filter membranes or filter membrane coatings. For at least these reasons, there is a continuing need in the filtration art for new and improved filters, including filters containing nylon. Summary of the Invention

[0006] The field of microelectronic device processing requires methods to maintain steady improvements in processing materials and parallel steady improvements in the performance (e.g., speed and reliability) of microelectronic devices. Opportunities for improving microelectronic device fabrication exist in all aspects of manufacturing processes, including methods and systems for filtering liquid materials.

[0007] In microelectronic device processing, a wide range of different types of liquid materials are used as process solvents, cleaning agents, and other processing solutions. Many, if not most, of these materials are used at extremely high levels of purity. As an example, the liquid materials (e.g., solvents) used in photolithographic processing of microelectronic devices must be of extremely high purity. Specific examples of liquids used in microelectronic device processing include spin-on-glass (SOG) technology, backside antireflective coating (BARC) methods, and processing solutions for photolithography. Some of these liquid materials are acidic. To provide these liquid materials at a high level of purity for use in microelectronic device processing, the filtering system must be highly effective at removing various contaminants and impurities from the liquid and must be stable (i.e., not degrade or introduce contaminants) in the presence of the liquid materials (e.g., acidic materials) being filtered.

[0008] In order to be able to provide a filter system with increasing effectiveness in challenging applications such as microelectronics processing, many important considerations are taken into account. Nylon materials (typically polyamides) have been used as porous filter membranes, as coatings on porous filter membranes, or both. Nylon has been used in filter membranes for filtering various liquid materials involved in microelectronic device fabrication, but as microelectronic device processing methods are constantly evolving, they are no longer effective or optimal unless improved upon.

[0009] As an example, metal ions are used as catalysts in the preparation of certain types of nylon materials and may be present in very small amounts in the finished nylon filter material. Even such low levels of metals in nylon filters can be problematic when using the filters in microelectronic device processing because the metals can be extracted from the nylon filter material by acidic liquids. The extracted metals become contaminants in the liquid. Apart from this, nylons vary in their ability to be processed into filter membranes. Nylons are designed to be stable and resistant to chemicals, which means that they may not be soluble in a wide range of solvents. Some nylons are soluble in certain types of solvents, such as acid solvents (e.g., formic acid) and ionic solvents (e.g., calcium chloride). However, each of these solvents has its drawbacks. Formic acid can be difficult to handle, and calcium chloride can leave impurities in the nylon coating that are unacceptable for the use of nylon as a filter for advanced node microelectronic device processing.

[0010] As described herein, applicants have determined that certain types of polyamides can be effectively coated onto porous polymeric filter layers to produce coated filter membranes that exhibit useful or advantageous filtration performance in filtering contaminants or impurities from liquid fluids. For example, the coated filter membranes can be used to remove contaminants from liquid materials, including acidic liquids, used in microelectronic device processing to produce filtered liquid materials having extremely high levels of purity.

[0011] The purity level of the treated liquid and the associated performance of the filter membrane can be measured using a variety of different techniques. In one quantitative measurement, the effectiveness of the filter material can be evaluated by testing the effectiveness of the filter material to remove known types and amounts of substances, e.g., "challenge" substances, which may be dissolved metals such as gold or metal particles. The coated filter membranes described herein can be highly effective at removing these types of challenge particles, e.g., based on these tests, can be at least as effective as current or previous filter membranes.

[0012] In another measurement, the effectiveness of a filter membrane may be measured in terms of its performance in a particular application, such as for filtering a fluid used in the processing of microelectronic or semiconductor devices, where the effectiveness of the filter membrane is measured in terms of performance, such as by measuring the level of defects present in a microelectronic or semiconductor device prepared using the fluid. As an example, the effectiveness of a filter membrane can be assessed by counting the number of defects, such as "bridge defects," present in a microelectronic or semiconductor device prepared using a liquid processing solution that is processed (i.e., filtered) using the filter membrane. Fewer defects in the device indicate a higher level of effectiveness of the filter membrane.

[0013] Polyamide may be coated onto the filter layer from a solvent using a different solvent, calcium chloride, different from formic acid, which are not optimal for use in treating nylon coatings of filters used in microelectronic device processing. The solvent (neither formic acid nor calcium chloride) may be non-acidic, non-ionic, and preferably can be handled and processed by conventional methods. Propanol, which is commonly and routinely handled in industrial applications, is one example of a solvent that can be used to dissolve the exemplary polyamide described. Propanol is non-acidic and does not introduce levels of contaminants into the coated polyamide that would make the polyamide unusable for microelectronic device applications.

[0014] The polyamide can be coated by any useful method, such as immersion precipitation, and may be crosslinked after coating to increase the solvent resistance of the polyamide.

[0015] In one aspect, the invention relates to a coated filter membrane that includes a porous polymeric filter layer and a non-porous crosslinked polyamide film coating on a surface of the porous filter layer.

[0016] In another aspect, the invention relates to a method of preparing a coated filter membrane, the method comprising: coating a polymer solution onto a surface of a porous filter membrane, the polymer solution comprising a polyamide polymer, a solvent and a free radical source material; coagulating the polyamide of the polymer solution on the surface; and crosslinking the polyamide. [Brief description of the drawings]

[0017] [Figure 1] 1 is a graph showing the dye binding capacity of various filter membranes. [Diagram 2] 1 is a graph showing the dye binding capacity of various filter membranes. [Diagram 3] 1 is a graph showing the dye binding capacity of various filter membranes. [Figure 4] 1 is a graph showing the dye binding capacity of various filter membranes. [Diagram 5] FIG. 1 shows data regarding the amount of metals extracted from filter membranes. [Figure 6] FIG. 1 shows data on the stability of polyamide coatings after exposure to low pH organic solvents. [Figure 7] FIG. 1 shows data on the stability of polyamide coatings after exposure to common photoresist solvents. [Figure 8] FIG. 1 shows data for coatings with varying amounts of photoinitiator. [Figure 9]FIG. 1 shows data regarding defect counts for different filter membranes. [Figure 10] FIG. 1 shows metal removal efficiency data for different filter membranes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The following description relates to coated filter membranes and methods of making the coated filter membranes, filter components and products such as filters containing the coated filter membranes, and methods of using the coated filter membranes, filter components or filters.

[0019] The coated filter membrane described includes a porous polymeric filter layer and a polymeric film coating on one or more surfaces of the porous polymeric filter layer. The polymeric film coating is a film coating that includes a crosslinked polyamide polymer. The polyamide may be dissolved in at least one solvent, different from formic acid and calcium chloride, which are often used to form a solution from nylon before crosslinking, but which may be difficult to handle (formic acid) or may produce unacceptable levels of residue or contaminants when the resulting nylon is used in a filter for microelectronic device processing (calcium chloride). In some embodiments, the polymeric film coating may be porous, and in other embodiments, the polymeric film coating may be non-porous.

[0020] The polyamide film coating may be a continuous or semi-continuous layer of a film containing polyamide that is applied to the surface of a porous polymeric filter layer. Preferred coatings are considered to be substantially thin as a "film". In some embodiments, the polyamide may be porous, while in other embodiments, the polyamide film may be non-porous or substantially non-porous (e.g., does not contain a substantial amount of void space). The film may be continuous or semi-continuous across the entirety of one or more surfaces of the porous polymeric film layer, i.e., the film may be discontinuous but may cover a substantial portion of the porous polymeric film layer.

[0021] A polymeric film coating containing crosslinked polyamide can be prepared by preparing a polymer solution containing a polyamide polymer (not crosslinked), disposing the polymer solution on the surface of a porous polymeric filter layer, and crosslinking the polyamide. The polymeric solution may be disposed on the surface of the polymeric filter layer in a manner effective to dispose a desired useful amount of polyamide on the outer and inner surfaces of the porous polymeric filter layer, for example, by precipitation coating. The polyamide polymer may then be crosslinked by any effective method. The crosslinked polyamide may be dried so that a continuous or semi-continuous porous or non-porous film coating remains on the surface of the filter layer, the film coating containing (comprises, consists of, or consists essentially of) the crosslinked polyamide polymer. The film coating may be present on a substantial portion of the inner surfaces of the pores of the porous polymeric filter layer and on the outer (macroscopic) surface of the porous polymeric filter layer.

[0022] Although the film coating may contain materials other than crosslinked polyamide, useful preferred examples of film coatings do not require any other materials. The described polyamide-containing film coatings after being applied, crosslinked, and dried may contain at least 50, 70, 85, 90, or 95 weight percent crosslinked polyamide, based on the total weight of the dried film coating. A film coating consisting essentially of a crosslinked polyamide coating is a film coating that contains no more than 5, 2, 1, or 0.5 weight percent of materials other than crosslinked polyamide.

[0023] The coated filter membrane may be useful for filtering liquids to remove undesired materials (e.g., contaminants or impurities) from the liquid and produce high purity liquids that can be used as materials in industrial processes. The industrial process may be any that requires high purity liquid materials as input materials, a non-limiting example of such a process includes a process for preparing microelectronic or semiconductor devices, a specific example of which is a method for filtering liquid processing materials (e.g., solvents or liquids containing solvents) used in semiconductor photolithography. Examples of contaminants present in processing liquids or solvents used to prepare microelectronic or semiconductor devices may include metal ions dissolved in the liquid, solid particulates suspended in the liquid, and gelled or solidified materials present in the liquid (e.g., generated during photolithography).

[0024] The coated filter membranes may be useful for removing dissolved or suspended contaminants or impurities (and the like) from a liquid that is made to flow through the coated filter membrane, either by sieving or non-sieving mechanisms, preferably by a combination of both non-sieving and sieving mechanisms. Sieving mechanisms are a type of filtration that removes particles from a liquid flow by mechanically retaining them on the surface of the filter membrane, where the filter membrane acts to mechanically interfere with the movement of the particles to retain them within the filter and mechanically prevent the particles from flowing through the filter. Typically, the particles may be larger than the pores of the filter. A "non-sieving" filtration mechanism is a type of filtration in which the filter membrane retains suspended particles or dissolved substances contained in the liquid flowing through the filter membrane in a mechanical manner, including but not limited to electrostatic mechanisms, for example.

[0025] In the exemplary coated filter membranes described, the porous polymeric filter layer may act to remove materials from the liquid stream passing through the coated filter membrane by a sieving mechanism, and the polymeric film coating comprising a polyamide polymer may act to remove materials from the liquid stream by a non-sieving mechanism.

[0026] The porous polymeric filter layer of the coated filter membrane may be any of the general range and types of porous polymeric filter materials used and useful in high purity liquid filtration applications. The porous polymeric filter layer may be characterized by its chemical makeup, general shape, and one or more of pore size, porosity, bubble point, and thickness, among other physical and performance features.

[0027] The shape may be a planar sheet extending in a length dimension and a width dimension and defining two opposing major surfaces separated in a third dimension by a thickness. The sheet may preferably have a relatively uniform thickness across the length dimension and the width dimension. An alternative shape may be a hollow fiber, which may include a length and a substantially uniform thickness extending between an inner diameter and an outer diameter.

[0028] A variety of different polymers are available for forming porous polymeric filter layers (e.g., membranes), some specific examples include non-fluorinated polymers such as polyolefins, polyhaloolefins, polyesters, polyimides, polyetherimides, polysulfones, polyethersulfones, polycarbonates, as well as fluoropolymers, and other general and specific types of useful polymers.

[0029] Suitable polyolefins include, for example, polyethylene (e.g., ultra-high molecular weight polyethylene (UPE)), polypropylene, alpha-polyolefins, poly-3-methyl-1-butene, poly-4-methyl-1-butene, and copolymers of ethylene, propylene, 3-methyl-1-butene, or 4-methyl-1-butene with each other or with minor amounts of other olefins; exemplary polyhaloolefins include polytetrafluoroethylene, polyvinylidene fluoride, and copolymers thereof with other fluorinated or non-fluorinated monomers. Exemplary polyesters include polyethylene terephthalate and polybutylene terephthalate, and related copolymers.

[0030] In some embodiments, the porous polymeric filter layer need not be fluorinated or perfluorinated, and may contain only non-fluorinated polymers made essentially from non-fluorinated monomers. Exemplary filter layers may include, consist of, or consist essentially of polyolefins such as polyethylene (e.g., UPE). Preferred polymeric filter layers in the present invention contain, consist of, or consist essentially of non-fluorinated polymeric materials. Porous polymeric filter layers essentially consisting of non-fluorinated materials may contain less than 0.5, 0.1, or 0.01 weight percent fluorine. Porous polymeric filter layers essentially consisting of polyolefins, such as polyethylene, may be derived from monomers that contain at least 99, 99.5, or 99.0 weight percent polyolefin (e.g., polyethylene) monomers.

[0031] Porous polymeric filters of any composition may optionally be treated, for example plasma treated, to enhance adhesion or filtering properties.

[0032] In some embodiments, the filter layer is made of a non-nylon polymer, such as a polyolefin, e.g., polyethylene, e.g., ultra-high molecular weight polyethylene (UPE). Nylon is often prepared using a metal catalyst, such as magnesium. The magnesium present in the filter layer can potentially be extracted when used in filtering certain types of liquids, such as acidic liquids. In some embodiments, the filter layer may be made of a non-nylon polymer to avoid the presence of such extractable metals. According to a useful example of the present invention, the coated filter membrane may include (may comprise, may consist of, or may essentially consist of) a non-nylon porous polymer filter layer (e.g., polyolefin, e.g., UPE filter membrane) coated with the crosslinked polyamide described. The metal (e.g., magnesium) content of the polyamide-coated non-nylon (e.g., UPE) porous polymer filter layer is substantially lower than the metal (e.g., magnesium) content of the equivalent nylon filter layer. A porous polymeric filter layer (e.g., a polyolefin, e.g., UPE filter membrane) may consist of or consist essentially of a non-nylon polymer; a porous polymeric filter layer consisting essentially of a non-nylon polymer is a filter membrane that contains no more than 5, 2, 1 or 0.5 weight percent nylon, based on the total weight of the filter membrane, for example, a filter membrane that contains at least 95, 98, 99 or 99.5 weight percent of a non-nylon polymer, such as a polyolefin (e.g., polyethylene, polypropylene, UPE, etc.), based on the total weight of the porous polymeric filter layer.

[0033] Exemplary porous polymeric filter layers may have pores of a size (average pore size) that qualify as either a microporous filter membrane or an ultrafiltration membrane. Microporous membranes may have an average pore size ranging from about 0.05 microns to about 10 microns, with the pore size being selected based on one or more factors, including the particle size or type of impurities to be removed, the pressure and pressure drop requirements, and the viscosity requirements of the liquid to be processed by the filter. Ultrafiltration membranes may have an average pore size ranging from 0.001 microns to about 0.05 microns. Pore size is often reported as the average pore size of the porous material, which can be measured by known techniques such as mercury porosimetry (MP), scanning electron microscopy (SEM), liquid displacement spectroscopy (LLDP) or atomic force microscopy (AFM).

[0034] Bubble point is also a known feature of porous membranes. In the bubble point test method, a sample of a porous polymeric filter layer is wetted by immersion in a liquid of known surface tension and gas pressure is applied to one side of the sample. The gas pressure is gradually increased. The minimum pressure at which the gas flows through the sample is called the bubble point. Examples of useful bubble points of porous polymeric filter layers useful or preferred according to the present specification may be in the range of 2 to 400 psi, for example, in the range of 20 to 200 psi, measured using an HFE7200 at a temperature of 20 to 25°C.

[0035] The described porous polymeric filter layers may have any porosity that allows the porous polymeric filter layers to be effective as described herein for filtering liquid streams to produce high purity filtered liquid materials. Exemplary porous polymeric filter layers may have a relatively high porosity, for example, at least 50, 60, 70, 80, 85, 90, 95 or 98 percent porosity, for example, in the range of 50, 60, 70, 80 or 85 to 90, 95 or 98 percent porosity. As used herein, and in the field of porous bodies, the "porosity" (sometimes referred to as porosity) of a porous body is a measure of the void (i.e., "empty") space of the body as a percentage of the body's total volume, calculated as the volume fraction of the voids of the body relative to the body's total volume. An object with zero percent porosity is completely solid.

[0036] The described porous polymeric filter layers may be in the form of sheets or hollow fibers having any useful thickness, for example, a thickness in the range of 5 to 100 microns, such as 20 to 50 microns.

[0037] According to the present specification, the physical characteristics of the coated filter membrane are substantially determined by and are equivalent or nearly equal to the corresponding physical characteristics of the porous polymeric filter layer.The porous polymeric filter layer may be selected based on physical characteristics including bubble point, porosity, pore size and thickness.After being coated with the non-porous film coating comprising crosslinked polyamide polymer as described, these physical characteristics may still be substantially the same or nearly the same for the coated filter membrane.

[0038] The coated filter membrane comprises the described polyamide film coating, for example, a continuous or semi-continuous film coating on the surface of the porous polymeric filter layer. The polyamide film coating is effective as a filtering component of the coated filter membrane, and includes crosslinked polyamides that improve the filtering performance (e.g., filtering effectiveness or retention) of the coated filter membrane by acting as a non-sieving filter medium. The polyamide may be selected for its filtering effectiveness and also for its processability. With regard to processability, preferred polyamides are those that can be effectively (and preferably efficiently) placed on the surface of the porous polymeric filter layer by a useful coating method before crosslinking, and then crosslinked to improve the solvent resistance of the polyamide.

[0039] To provide the desired processability, the preferred polyamide can be dissolved in a solvent to form a polymer solution that can be coated on the surface of the porous polymer filter layer in a desired amount, and then precipitated from the polymer solution onto the surface of the porous polymer filter layer, i.e., the preferred polyamide can be dissolved in a solvent and precipitated onto the surface of the porous polymer filter layer. The amount and arrangement of the polyamide material coated on the surface should be sufficient to allow the polyamide to improve the filtering performance of the porous polymer filter membrane, but should not cause any unacceptable adverse effect on the flow or filtering properties of the porous polymer filter membrane, for example, significantly reducing the ability of liquid to flow through the porous polymer filter membrane when used as a filter.

[0040] The crosslinked polyamide may be effective to act as a filtration material as described herein, preferably in a pre-crosslinked form that may be provided as a coating of a porous polymeric film coating by any useful coating technique, for example, preferably by precipitation coating from a copolymer solution in which the polyamide (prior to crosslinking) is dissolved in a solvent as described herein.

[0041] Polyamides are a well-known class of polymers that includes nylon. Polyamides are chemically considered to be polymers that contain a plurality of repeating carbon-based organic polymer backbone units separated by repeating amide bonds. The term "polyamide" refers to polymers including those derived from two or more reactive monomeric compounds with repeating amide groups (e.g., polyamide "copolymers" and "terpolymers"), as well as blends of two or more different such polyamides.

[0042] Polyamides can be prepared by reacting monomers or reactive materials that contain combinable functional groups to form a polymer backbone with repeating amide bonds. Thus, examples of monomers and reactive materials useful for preparing polyamides include diamine monomers and dicarboxylic acid monomers. Exemplary polyamides include copolymers and terpolymers prepared by polymerizing combinations of two or three diamine and dicarboxylic acid monomers.

[0043] Useful monomers, such as diamines or dicarboxylic acids, may be linear, containing a saturated linear hydrocarbon compound and two functional groups, e.g., two amine or two carboxylic acid groups. These compounds react to form linear (e.g., aliphatic) units of the polyamide backbone. Other useful monomers may be compounds containing two functional groups, e.g., amine or carboxylic acid groups, attached to non-linear compounds, such as aromatic compounds or saturated cyclic or bicyclic compounds. These compounds react to form non-linear units, e.g., cyclic or polycyclic units of the polyamide backbone.

[0044] In some embodiments, the polyamides herein useful for film coating of coated filter membranes may include linear and non-linear backbone units, for example, may be derived by reacting linear and non-linear monomers to produce polyamides having backbone units including linear and non-linear backbone units. The non-linear backbone units may preferably be effective to increase the ability of the polyamide in an uncrosslinked state to dissolve in a desired solvent to form the described polymer solutions.

[0045] Certain specific non-limiting examples of linear compounds (monomers) that may be useful in preparing the polyamides described herein include caprolactam, hexamethylenediamine adipate, and combinations thereof. A specific non-limiting example of a non-linear compound (monomer) that may be useful in preparing the polyamides described herein is 4,4-diamino-dicyclohexylmethane adipate. These exemplary monomers should not be construed as limiting the types of monomers or reactive materials that can be used to prepare the polyamides useful herein. Other linear monomers (e.g., linear diamines and linear dicarboxylic acid groups) are also useful for preparing the polyamides described herein, as are other non-linear monomers (e.g., diamines and dicarboxylic acid compounds that contain a cyclic 6-membered saturated ring structure (e.g., a divalent cycloalkylene residue) or two linked cyclic 6-membered saturated ring structures (e.g., a divalent dicycloalkylene residue).

[0046] The described polyamides may be made of repeating amide groups, preferably separated by a combination of linear and non-linear backbone units that make the polyamide solvent-processible in the described desired solvents other than formic acid and calcium chloride. A polyamide is considered solvent-processible if it can be dissolved in a solvent before crosslinking to form a polymer solution that can be applied to a porous polymer filter layer as a coating. The polyamide is preferably fully soluble in the solvent in a sufficient amount that the polyamide can form a polymer solution that is useful for coating, for example, by immersion precipitation.

[0047] The polyamide, as well as certain polyamides and nylons, need not be melt processable, e.g., thermoplastic, meaning that the polyamide can be converted, e.g., repeatedly, between a liquefied (molten) state and a solid state without substantial degradation.

[0048] It is known that various polyamides are solvent processable using certain types of solvents, such as some acidic solvents (e.g., formic acid) and certain ionic solvents (e.g., calcium chloride). For example, some nylons, such as nylon 66, are soluble in formic acid and calcium chloride, but generally not soluble in other organic materials. However, formic acid can be difficult to handle. Also, calcium chloride is not a preferred solvent for use in preparing nylon materials for filters used to filter high purity liquids, such as those used in semiconductor processing, due to the resulting unacceptable levels of impurities in the nylon materials coated from calcium chloride.

[0049] Preferred non-crosslinked polyamide materials herein may be solvent processable in solvents different from formic acid and different from calcium chloride. More generally, certain useful preferred non-crosslinked polyamides may be soluble in a variety of non-acidic solvents, such as organic solvents (optionally containing a water component), which are easier to handle compared to formic acid and calcium chloride and do not result in undesirable residues present in the coated polyamide for use in filters for processing high purity materials.

[0050] Useful or preferred non-crosslinked polyamides herein may be soluble in at least one alternative solvent, i.e., a solvent that may be made solely from (e.g., consisting of, or essentially of) a solvent that is different from formic acid and different from calcium chloride, and preferably does not contain formic acid or calcium chloride. A solvent that essentially consists of a solvent different from formic acid and calcium chloride refers to a solvent that contains no more than 5, 2, 1, or 0.5 weight percent formic acid or calcium chloride, with one or a combination of a solvent different from formic acid and calcium chloride, and optionally water.

[0051] Examples of alternative solvents include a variety of organic, non-acidic, non-ionic solvents that are commonly used, handled and processed in various industrial and commercial processes and that can be used to dissolve the non-crosslinked polyamide and form a coating of the polyamide without unacceptable amounts of solvent-derived residue, such that the solvent dissolves the non-crosslinked polyamide in a useful and sufficient amount to enable the solvent to become a vehicle for coating a desired amount of the non-crosslinked polyamide onto a substrate, such as a porous polymeric filter layer, by a dip-precipitation coating method.

[0052] Examples of solvents different from formic acid and different from calcium chloride that are preferred in the present invention include lower aliphatic alcohols (e.g., C1-C3, C4, C5 or C6 aliphatic alcohols), such as methanol, ethanol, propanol, butanol, isopropanol, and chlorinated hydrocarbons. Useful or preferred non-crosslinked polyamides herein are soluble in one or a combination of these solvents, optionally in combination with water, to the extent that the non-crosslinked polyamide can be coated from the solvent onto a porous polymeric filter layer as described herein. Certain preferred non-crosslinked polyamides in the present invention are soluble in a solvent made of or consisting essentially of propanol and optional water, for example, made of only propanol, optionally in combination with 20 weight percent or less of water based on the total weight of the solvent.

[0053] Thus, useful or preferred solvents may comprise, consist of, or consist essentially of solvents including one or combinations of the following, further optionally in combination with amounts of water: lower aliphatic alcohols such as methanol, ethanol, propanol, butanol, isopropanol, and the like; and one or more chlorinated hydrocarbons. The solvent may optionally contain an amount of water, for example, up to about 20, 10, or 5 percent water.

[0054] A solvent consisting essentially of a particular solvent or combination of solvents (including water in an amount optional) is a solvent that contains the particular solvent or combination of solvents and not more than 5, 2, 1, or 0.5 weight percent of a material (e.g., solvent) different from the particular solvent or solvents. A solvent consisting essentially of one or a combination of lower aliphatic alcohols such as methanol, ethanol, propanol, butanol, isopropanol, etc., chlorinated hydrocarbons, or combinations thereof, optionally including water, is a solvent that contains one or a combination of these solvents and, optionally, water and not more than 5, 2, 1, or 0.5 weight percent of any other material.

[0055] Depending on the solvent, heating may be used to enable or facilitate dissolution of the non-crosslinked polyamide into the solvent. For example, in the absence of heating, the non-crosslinked polyamide may take many hours or days to completely dissolve in the solvent as described. For example, by heating the solvent to a temperature in the range of 60-80°C, the time is shortened. Preferably, by heating, the non-crosslinked polyamide described can be completely dissolved in the solvent in a few hours (e.g., 2, 4 or 6 hours) or less (e.g., less than 40, 30, 20 or 10 minutes).

[0056] According to some embodiments of the polyamide and method herein, polyamide can be dissolved in a solvent to form a polymer solution that can be applied to a porous polymer filter layer by immersion precipitation, followed by crosslinking the polyamide.A typical method includes one or more steps, including: forming or otherwise providing a polymer solution that includes non-crosslinked polyamide dissolved in a solvent (the formic acid-free and calcium chloride-free solvent described herein, including an optional amount of water) together with a free radical source material; applying the polymer solution to a porous polymer filter layer; precipitating (coagulating) the polyamide of the polymer solution from the solution onto the porous polymer filter layer; crosslinking the polyamide coated on the porous polymer filter layer; and drying the polyamide.

[0057] Precipitating a polymer from a polymer solution onto a filter layer, also known as immersion precipitation or phase inversion, is a commonly known method of disposing a polymer film onto a substrate. In this technique, as applied to the polyamide and polymer solutions herein, a polymer solution containing a polyamide is coated onto a porous polymer filter layer, and the polyamide of the polymer solution may be precipitated from the polymer solution onto the porous polymer filter layer by contacting the polymer solution-coated filter layer with a coagulation liquid containing a non-solvent, such as an aqueous liquid (e.g., by immersing the coated filter layer in a coagulation bath). Due to the exchange of solvent and non-solvent that occurs when the polymer solution is exposed to the coagulation liquid, the polymer (i.e., non-crosslinked polyamide) precipitates from the polymer solution onto the surface of the film layer onto which the polymer solution is coated. The polymer must be soluble in the solvent of the polymer solution and must precipitate or coagulate when contacted with the non-solvent of the coagulation liquid (e.g., an aqueous liquid).

[0058] The polymer solution contains any effective amount of each of the solvent, dissolved polyamide, and free radical source material. Exemplary polymer solutions may contain up to about 10 or 20, e.g., 0.5-8 or 0.5-5 or 3 weight percent polyamide, up to about 5, e.g., 0.5-6 or 1-5 weight percent free radical source material, based on the total weight of the polymer solution, with the remainder being solvent (e.g., an organic solvent as described herein, optionally combined with an amount of water).

[0059] Exemplary polymer solutions do not require and may exclude acidic solvents such as formic acid and ionic solvents such as calcium chloride. A preferred solvent may be propanol, optionally with water, although other solvents, including the exemplary solvents described herein that are non-acidic, non-basic and non-ionic, may be used alone or in combination with propanol.

[0060] The polymer solution may comprise, consist of, or consist essentially of polyamide, free radical source material, and solvent (e.g., as described and exemplified herein). A polymer solution consisting essentially of polyamide, free radical source material, and solvent (e.g., as described and exemplified herein) refers to a polymer solution containing at least 95, 98, 99, or 99.5 weight percent polyamide, free radical source material, and solvent (e.g., as described and exemplified herein), and up to 0.5, 1, 2, or 5 weight percent of any other materials.

[0061] After the polyamide is precipitated on the surface of the filter layer, the polyamide may be crosslinked to increase the solvent resistance of the polyamide. Crosslinked polyamide refers to a polyamide in which the polymer chains of the polyamide composition (e.g., the coated and precipitated polyamide) are chemically crosslinked with each other; thus, at least one polyamide chain is crosslinked (chemically bonded) with at least one other polyamide chain at at least one position, where optionally there are multiple bonds between one single polyamide chain and one, two or more other polyamide chains.

[0062] Crosslinking can occur by any useful mechanism, with a preferred method being exposing the coated polyamide material to a free radical source material and a radiation source, such as ultraviolet (UV) radiation. Useful examples of free radical source materials are well known and include photoinitiators such as benzoin, benzoin ethyl ether, benzophenone, benzophenone derivatives, Michler's ketone, alphahydroxyketones, benzil dimethyl ketal, isopropylthioxanthan, dialkoxyacetophenones such as diethoxyacetophenone, substituted benzoins such as acetophenone, benzil, peroxides and other derivatives (substituted forms), and mixtures thereof. An example of a preferred free radical source material is benzophenone. This or another free radical source material may be used in combination.

[0063] Optionally, if desired, the polymer solution may include one or more additional multifunctional, e.g., polyfunctional compounds that increase the level of crosslinking between the polyamide chains of the polymer solution. A crosslinking agent is not required, and the exemplary polymer solution does not require, and may exclude, the presence of a multifunctional crosslinking agent in addition to the polyamide polymer.

[0064] The method used to induce crosslinking of the polyamide may be any method useful for resulting in a crosslinked polyamide having increased resistance to solvents compared to non-crosslinked polyamide. Methods other than the use of UV radiation and a free radical source may be useful, for example, by the use of e-beam radiation.

[0065] The described crosslinked polymers coated on the porous polymeric filter as part of the coated filter membrane can be characterized in terms of the dye-binding capacity of the crosslinked polymer. In particular, a charged dye can be attached to the surface of the crosslinked polymer. The amount of dye that can be attached to the crosslinked polymer can be quantitatively measured by spectroscopy based on the difference in the measured film absorption readings at the absorption frequency of the dye obtained before and after the application of the crosslinked polyamide. The dye-binding capacity can be evaluated using a negatively charged dye or a positively charged dye.

[0066] In some embodiments, a filter membrane coated with a crosslinked polyamide may have a dye-binding capacity for positively charged dyes, negatively charged dyes, or both, when evaluated using the same run or test conditions, that is greater than a comparable filter made from or coated with certain previously used polyamides, such as nylon 6 or nylon 66. The described coated filter membranes may have a dye-binding capacity for methylene blue dye of at least 0.2 micrograms per milligram of filter membrane (μg / mg), e.g., greater than 0.5 or 1.0 μg / mg; alternatively or in addition, the described coated filter membranes may have a dye-binding capacity for Ponceau S dye of at least 0.2 micrograms per milligram of filter membrane (μg / mg), e.g., greater than 0.05, 0.25, 0.5, or 0.6 μg / mg.

[0067] In some embodiments, the crosslinked polyamide coated filter membranes disclosed herein extract more than 1.0 ng / cm of magnesium (Mg) from a sample of the membrane having a diameter of 47 mm and a thickness of 55 microns, when the sample is immersed in 15 ml of 0.1 N HCl solution (hydrochloric acid) for 24 hours. 2 (nanograms per square centimeter), 0.9ng / cm 2 , 0.8ng / cm 2 , 0.7ng / cm 2 , 0.6ng / cm 2 , 0.5ng / cm2 or 0.4ng / cm 2 The amount of Mg is measured by inductively coupled plasma mass spectrometry (ICP-MS). The crosslinked polyamide film coating on the porous polymer filter may be optionally treated, for example, plasma treated, to enhance filtering properties.

[0068] As part of the desired coating properties of polyamide, the crosslinked and dried polyamide film coating should not close the pores of the porous film layer to an unacceptable degree, e.g., should not cause unacceptable changes in the flow properties of the porous polymeric filter layer of the coated filter membrane. The flow rate and flow velocity of the liquid through the coated film membrane (i.e., the porous polymeric film coating after the polyamide film coating is placed on the porous polymeric film layer) should be sufficient and acceptable for the coated film membrane to function as a commercial filter membrane. In a preferred example of a method that can provide the described coating, the polyamide may be coated on the porous polymeric filter layer by applying a polymer solution containing a (non-crosslinked) polyamide dissolved in a solvent onto the surface of the porous polymeric filter layer and allowing the (non-crosslinked) polyamide to precipitate (coagulate) from the polymer solution onto the surface of the filter layer. The precipitated (non-crosslinked) polyamide covers the surface of the porous polymeric filter layer in an amount such that the coated polyamide, after crosslinking and drying, effectively functions as a non-sieving filter medium without significantly blocking the openings in the porous filter membrane, i.e., without reducing the flow through the membrane by more than 30, 20, 10 or 5 percent (measured based on flow rate or as a 5, 10, 20 or 30 percent increase in flow time).

[0069] The filter membranes described herein, or filters or filter components containing the filter membranes, may be useful in methods of filtering liquid chemicals to purify or remove unwanted materials from the liquid chemicals, particularly to produce extremely pure liquid chemicals, which are useful in industrial processes that require input of chemicals with extremely high levels of purity. In general, the liquid chemicals may be any of a variety of useful commercial materials, or may be liquid chemicals useful or used in any application for any industrial or commercial use. Particular examples of the filters described may be used to filter liquid solvents or other process fluids used in semiconductor or microelectronic fabrication applications, or to purify useful liquid chemicals, for example, for use in semiconductor photolithography methods. Some specific non-limiting examples of solvents that may be filtered using the described filter membranes include n-butyl acetate (nBA), isopropyl alcohol (IPA), 2-ethoxyethyl acetate (2EEA), xylene, cyclohexanone, ethyl lactate, methyl isobutyl carbinol (MIBC), methyl isobutyl ketone (MIBK), isoamyl acetate, undecane, propylene glycol methyl ether (PGME), and propylene glycol monomethyl ether acetate (PGMEA).

[0070] To be useful for filtering liquid chemicals, such as solvents, the crosslinked polyamides described must be resistant to the liquid chemicals being filtered, e.g., must be substantially resistant to degradation in the presence of these liquids. Preferred crosslinked polyamide materials are resistant to the liquid chemicals being filtered (e.g., solvents or acids) and are effective in processing the liquid chemicals by filtration to produce liquid chemicals having very low levels of dissolved impurities such as metals, and very low levels of suspended particles or other impurities or contaminants.

[0071] The coated filter membrane may be contained within a larger filter structure, such as a filter or filter cartridge used in a filtering system. The filtering system places the coated filter membrane in a flow path of a liquid chemical, for example as part of a filter or filter cartridge, and allows the liquid chemical to flow through the coated filter membrane so that the coated filter membrane can remove impurities and contaminants from the liquid chemical. The filter or filter cartridge structure may include one or more of a variety of additional materials and structures that support the coated filter membrane within the filter and allow the fluid to flow from the inlet of the filter through the coated membrane to the outlet of the filter, thereby passing through the coated filter membrane as it passes through the filter. The coated filter membrane supported by the filter structure may be in any useful shape, for example, a pleated cylinder, a cylindrical pad, one or more non-pleated (flat) cylindrical sheets, a pleated sheet, among others.

[0072] An example of a filter structure comprising a coated filter membrane in the form of a pleated cylinder can be prepared to include the following components, any of which may be included in the filter construction but are not required: a rigid or semi-rigid core that supports the pleated cylindrical coated filter membrane at the inner opening of the pleated cylindrical coated filter membrane; a rigid or semi-rigid cage that supports or surrounds the exterior of the pleated cylindrical coated filter membrane at the exterior of the filter membrane; optional tips or "pucks" located at each of the two opposite ends of the pleated cylindrical coated filter membrane; and a filter housing that includes an inlet and an outlet. The filter housing may be of any useful desired size, shape and material, and may preferably be made of a suitable polymeric material. EXAMPLES

[0073] Porosimetry Bubble Point The porosimetry bubble point test measures the pressure required to force air through the wetted pores of a membrane and is a well-known method for determining the pore size of a membrane.

[0074] Flow velocity measurement The flow rate of isopropanol (IPA) was determined by cutting the membrane into a 47 mm disk, wetting it with IPA, and then placing the disk in a filter holder equipped with a reservoir to hold a volume of IPA. The reservoir is connected to a pressure regulator. IPA was flowed through the membrane under a differential pressure of 14.2 psi (pounds per square inch). After equilibrium was achieved, the time it took for 10 ml of IPA to flow through the membrane was recorded.

[0075] Example 1 This example describes the preparation of a 14 wt% polyamide stock solution. In a round bottom flask equipped with a stir bar and condenser, 14 grams of Ultramid 1C (BASF) resin was added to a mixture of 86 g of 1-propanol (Sigma) / DI water. The mixture was prepared by mixing 20 ml of DI water with 80 ml of 1-propanol. The mixture was heated under reflux for 10 hours until all the resin was dissolved. The resulting solution was clear and free of undissolved solids.

[0076] Example 2 This example describes the preparation of a polyamide coating solution.

[0077] A solution was made containing 2 g of benzophenone (Sigma), 28.57 g of the stock solution prepared in Example 1, and 69.43 g of a mixture of propanol:water (80:20 Vol%). Mixing was continued for 30 minutes until the benzophenone was completely dissolved.

[0078] Example 3 This example demonstrates the coating of a UPE membrane with polyamide.

[0079] A 47 mm UPE disk (average HFE bubble point 99 psi) was wetted with the coating solution described in Example 2 for 10 seconds. The membrane disk was removed and placed between 1 mil polyethylene sheets. A rubber roller was rolled over the polyethylene / membrane disk / polyethylene sandwich laying flat on a table to remove excess solution. The UPE membrane was removed from the sandwich and immediately placed in deionized (DI) water and swirled for 2 minutes to wash and precipitate the coating solution on the surface of the porous membrane disk. The membrane disk was removed and again placed between 1 mil polyethylene sheets. A rubber roller was rolled over the polyethylene / membrane disk / polyethylene sandwich laying flat on a table to remove excess water. The polyethylene sandwich was then taped to a transport device, which transported the assembly into a Fusion Systems broadband UV exposure laboratory that emits light at wavelengths from 200 nm to 600 nm. The exposure time is controlled by the speed at which the assembly moves through the UV device. In this example, the assembly moved through the UV chamber at 8 feet per minute. After exiting the UV unit, the membrane was removed from the sandwich and immediately placed in a 60 wt% isopropanol solution containing 2.5 wt% HCl and swirled for 12 hours. The coated membrane disk was then swirled for an additional hour in a 100% isopropanol solution. Following this washing procedure, the membrane was dried on a holder in an oven operating at 50° C. for 10 minutes.

[0080] The average isopropanol flow rate for the six coated membrane disk samples was 5.1 ml / min. The average flow rate for the three uncoated membrane samples tested was 6.2 ml / min. The average HFE bubble point for the six coated membrane disk samples was 96 psi.

[0081] Example 4 This example demonstrates the methylene blue dye binding ability of UPE disks prepared in the manner described in Example 3. This example further demonstrates that the process of Example 3, when carried out with the coating solution of Example 2, results in a UPE membrane capable of binding a positively charged dye.

[0082] Three water-wet 47 mm coated membrane disks from Example 3 were placed into a beaker containing 50 ml of 0.00075 wt% methylene blue dye (Sigma) adjusted to pH 10 with 10 M sodium hydroxide. The beaker was covered and the coated membrane disks were soaked for 2 hours with continuous mixing at room temperature. The disks were then removed and the absorbance of the dye solution was measured using a Cary spectrophotometer (Agilent Technologies) operating at 664 nm. The membranes were rinsed with water and soaked in 50 ml of 100% isopropanol for 30 minutes. This step desorbs any dye molecules nonspecifically bound to the membrane surface. Nonspecific adsorption refers to dye molecules that are not bound to the coated membrane surface by electrostatic interactions. The membrane disks were then removed and the absorbance of the isopropanol solution was measured using a Cary spectrophotometer (Agilent Technologies) operating at 656 nm.

[0083] Using the slopes of the calibration curves shown in Figures 1 and 2, the absorbance data of the dye solution before and after soaking the membrane and the absorbance data of the isopropanol solution were converted to mass of methylene blue dye bound to the membrane per unit mass of membrane. The dye is cationic and bound to negatively charged groups imparted to the membrane by the polyamide coating with an average dye-binding capacity of 1.4 μg / mg. In contrast, the average dye-binding capacity of uncoated UPE membranes was 0.1 μg / mg under similar experimental conditions.

[0084] Example 5 This example demonstrates the Ponceau S dye binding ability of UPE disks prepared in the manner described in Example 3. This example further demonstrates that the process of Example 3, when carried out with the coating solution of Example 2, results in a UPE membrane capable of binding a negatively charged dye.

[0085] Three water-wet 47 mm coated membrane disks from Example 3 were placed into a beaker containing 50 ml of 0.002 wt% Ponceau S dye (Sigma) solution. The beaker was covered and the coated membrane disks were allowed to soak for 2 hours with continuous mixing at room temperature. The disks were then removed and the absorbance of the dye solution was measured using a Cary spectrophotometer (Agilent Technologies) operating at 518 nm. The membranes were rinsed with water and soaked in 50 ml of 100% isopropanol for 30 minutes. This step desorbs any dye molecules non-specifically bound to the membrane surface. The membrane disks were then removed and the absorbance of the isopropanol solution was measured using a Cary spectrophotometer (Agilent Technologies) operating at 501 nm.

[0086] The absorbance data of the dye solution before and after soaking the membrane and the absorbance data of the isopropanol solution were converted to mass of dye bound to the membrane per unit mass of membrane using the slopes of the calibration curves shown in Figures 3 and 4. The dye was anionic and bound to positively charged groups imparted to the membrane by the polyamide coating with an average dye-binding capacity of 0.75 μg / mg. In contrast, the average dye-binding capacity of uncoated UPE membranes was 0.05 μg / mg under similar experimental conditions.

[0087] Example 6 This example demonstrates the methylene blue and Ponceau S dye binding capacity of nylon 6,6 membranes.

[0088] One water-wet 47 mm section of nylon 6,6 membrane with an average HFE bubble point greater than 100 psi was immersed in 50 ml of methylene blue or Ponceau S dye solution as described in Examples 4 and 5. The membrane bound methylene blue with an average dye-binding capacity of 5.4 μg / mg and Ponceau S with an average dye-binding capacity of 4.3 μg / mg.

[0089] Example 7 This example demonstrates the methylene blue and Ponceau S dye binding capacity of nylon 6 membranes.

[0090] One water-wet 47 mm section of nylon 6 membrane with an average HFE bubble point of 62 psi was immersed in 50 ml of methylene blue or Ponceau S dye solution as described in Examples 4 and 5. The membrane bound methylene blue with an average dye-binding capacity of 1.4 μg / mg and Ponceau S with an average dye-binding capacity of 10.7 μg / mg.

[0091] Example 8 This example demonstrates that polyamide-coated UPE membranes are cleaner than nylon 6 membranes with respect to extractable metals in low pH solutions.

[0092] A 47 mm disk of nylon 6 membrane and a 47 mm disk of the membrane prepared in Example 3 were extracted with 0.1 N HCl. ICP-MS was used to quantitate the amount of metals extracted. As shown in Figure 5, 40 ng / cm2 of Mg was extracted from the nylon 6 membrane compared to 0.4 ng / cm2 of Mg extracted from the polyamide coated UPE membrane. The total metals extracted from the nylon 6 and polyamide coated UPE membranes were 90 ng / cm2 and 33 ng / cm2, respectively.

[0093] Example 9 This example demonstrates that polyamide-coated UPE membranes are stable in low pH organic solvents.

[0094] UPE-coated polyamide membrane samples were immersed in a 60 wt% isopropanol solution containing 3.5 wt% HCl for 9 days. The amount of polyamide on the membrane surface at time 0 and after immersion in the low pH organic solvent was determined in the form of peak ratios by ATR-FTIR ("ATR") spectroscopy. ATR measurements were performed using a Bruker Tensor27FTIR fitted with an ATR assembly housing a germanium crystal. All spectra were recorded with 32 scans at a resolution of 4 cm-1. The background was bare crystal. The peak areas at 1713 and / or 1496 cm-1 (corresponding to the amide stretch) were obtained using the OPUS data collection program and the sum was divided by the total peak areas at 2918 and 2850 cm-1 (corresponding to the UHMWPE stretch) to obtain the amount of acrylamide monomer grafted onto the UHMWPE (ultra-high molecular weight polyethylene) surface. The UHMWPE signal is used as a conventional internal standard to normalize for differences in absolute absorbance intensity of the amide peak that may result from variations in modification levels between membrane discs.

[0095] As shown in Figure 6, the amount of polyamide coated on the membrane surface did not decrease after exposure to low pH organic solvents, suggesting that the polyamide coating is stable in photoapplications such as BARC, ITC and SOG, which are acidic.

[0096] Example 10 This example demonstrates that polyamide-coated UPE films are stable in common photoresist solvents.

[0097] UPE-coated polyamide membrane samples were immersed in cyclohexanone, OK73, and ArF thinners (PGMEA 45-55%, HBM 35-45%, EL 5-15%) for 5 days. The amount of polyamide on the membrane surface at time 0 and after immersion in the organic solvent for 5 days was determined in the form of peak ratios by ATR-FTIR ("ATR") spectroscopy, as described in Example 8. As shown in FIG. 7, the amount of polyamide coated on the membrane surface was essentially the same before and after immersion.

[0098] Example 11 This example compares the concentration of benzophenone in coating formulations.

[0099] A 47 mm section of UPE membrane (average HFE bubble point 80 psi) was coated with polyamide according to the process described in Example 3 using concentrations of 3 wt% Ultramid 1C and 0.5, 1 or 2 wt% benzophenone. After exiting the UV unit, the membrane section was removed from the polyethylene sheet sandwich and immediately placed in a Soxhlet extractor containing 100% isopropanol. Extraction was carried out for 24 hours. The amount of polyamide on the membrane surface at time 0 and after extraction with isopropanol was determined in the form of peak ratios by ATR-FTIR ("ATR") spectroscopy as described in Example 8. As shown in FIG. 8, the amount of polyamide coated on the membrane surface was reduced by approximately 45, 12 and 2% with concentrations of benzophenone of 0.5, 1 and 2 wt%, respectively.

[0100] Example 12 This example demonstrates that when lithography solutions were filtered through a filtration device containing a membrane (UPE, average HFE bubble point 100 psi) coated according to the process described in Example 3, the resulting wafer defect counts were reduced.

[0101] The filter device was filled with TOK OK73 solvent (PGME:PGMEA 70:30) and flushed with 6 liters of solvent. Lithography work was performed on ASML 1970i and TEL LITHIUS Pro-Zi track coating and developing systems with 1.35NA. For defectivity testing, a mask with only the L45P100 pattern was used with full-field exposure. For pattern defectivity testing, PT-CAR AIM5484 (JSR) material coated on ARC-29SR-309 (BSI) was used. Bare silicon wafers are coated with PT-CAR (AIM5484) resist on ARC (ARC-29SR-309). The wafers were exposed with the mask characteristic L45P100 pattern with full-field exposure. The patterned wafers were measured on a KLA2925 using standard recipes. The defects were rechecked and classified using a KLA eDR-7100.

[0102] As shown in FIG. 9, the polyamide coated UPE membrane exhibited the lowest defect count (best performance) at 6±1 compared to 9±1 and 20±1 for the nylon 6 (average HFE bubble point 60 psi) and UPE membranes (average HFE bubble point 100 psi), respectively.

[0103] Example 13 Example of Solvent Filtration for Metal Contaminant Removal UPE membranes (average HFE bubble point 80 psi) were coated with polyamide according to the process described in Example 3 and cut into 47 mm membrane sections. The membrane sections were conditioned by washing several times with 10% HCl, followed by overnight soaking in 10% HCl and equilibrating with deionized water. One 47 mm membrane section for each sample was fixed to a clean PFA 47 mm Single Stage Filter Assembly (Savillex). The membrane and filter assembly were flushed with IPA, followed by coating solvent. The coating solvent was PGMEA. The coating solvent was spiked with CONOSTAN Oil Analysis Standard S-21 (SCP Science) at a target concentration of 5 ppb for each metal. To determine the metal removal efficiency of the filtration, the metal-spiked coating solvent was passed through the corresponding 47 mm filter assembly containing each filter at 10 mL / min, and the filtrate was collected in 100 mL, 150 mL, and 200 mL clean PFA jars. The metal concentrations of the metal-spiked coating solvent and each filtrate sample were determined using ICP-MS.

[0104] Results are shown in comparison to a nylon 6 membrane (average HFE bubble point 62 psi, adjusted with 0.35% HCl) in total metal rejection (%) in Table 10 and individual metal rejection (% PGMEA) per 200 mL filtration in Figure 10. The polyamide coated UPE membrane has metal removal efficiency comparable to that of the nylon 6 membrane. However, the polyamide coated UPE membrane shows improved removal of individual metals at least for Al, Ti, Cr, Mn, Fe, Ni and Sn when compared to the nylon 6 membrane. TIFF2025060678000002.tif30170

Claims

1. a porous polymeric filter layer, and A non-porous cross-linked polyamide film coating on the surface of a porous filter layer A coated filter membrane comprising:

2. 2. The coated filter membrane of claim 1, wherein the polyamide comprises a backbone having cyclic bonds.

3. 3. The coated filter membrane of claim 2, wherein the cyclic linkage is a dicyclohexenyl linkage.

4. 4. The coated filter membrane of claim 1, wherein the polyamide is derived from non-linear monomers selected from caprolactam, hexamethylenediamine adipate, and cyclic and bicyclic reactive compounds.

5. The coated filter membrane of claim 4, wherein the non-linear polymer is 4,4-diamino-dicyclohexylmethane adipate.

6. 6. The coated filter membrane of claim 1, wherein the membrane has a dye binding capacity for methylene blue dye of at least 0.2 micrograms per milligram of membrane.

7. From a sample of the membrane having a diameter of 47 mm and a thickness of 55 microns, a concentration of 1.0 ng / cm was measured by inductively coupled plasma mass spectrometry (ICP-MS) when the sample was immersed in 15 ml of 0.1 N HCl solution for 24 hours. 2 7. The coated filter membrane of claim 1 , wherein less than 10 ...

8. 8. The coated filter membrane of claim 1 further comprising a residual free radical source material.

9. 9. The coated filter membrane of claim 1, wherein the porous polymeric filter layer has a porosity of at least 50 percent.

10. The coated filter membrane of any one of claims 1 to 9, wherein the porous polymeric filter layer has a pore size in the range of 0.001 to 10 microns.

11. 11. The coated filter membrane of any one of claims 1 to 10, having a bubble point in the range of 2 to 400 psi, measured using an HFE 7200 at a temperature of 20 to 25°C.

12. The coated filter membrane of any one of claims 1 to 11, wherein the porous polymeric filter layer has a thickness in the range of 5 to 100 microns.

13. 13. The coated filter membrane of any one of claims 1 to 12, wherein the porous polymeric filter layer comprises a polymer selected from polyethylene and polypropylene.

14. 14. The coated filter membrane of any one of claims 1 to 13, wherein the porous polymeric filter layer is ultra-high molecular weight polypropylene.

15. 15. The coated filter membrane of any one of claims 1 to 14, wherein the crosslinked polyamide membrane is resistant to propylene glycol methyl ether (PGME), propylene glycol methyl ether acetate (PGMEA) or cyclohexanone.

16. A filter cartridge comprising the coated filter membrane of any one of claims 1 to 15.

17. A filter comprising a coated filter membrane according to any one of claims 1 to 15.

18. 16. A method of using the coated filter membrane of any one of claims 1 to 15, comprising passing a solvent-based liquid through the membrane.

19. 20. The method of claim 18, wherein the liquid comprises a solvent selected from propylene glycol methyl ether (PGME), propylene glycol methyl ether acetate (PGMEA) and cyclohexanone.

20. 20. The method of claim 18 or 19, wherein the coated filter membrane removes one or more of Al, Ti, Cr, Mn, Fe, Ni or Sn from the solvent-based liquid.

21. Coating a polymer solution onto a surface of a porous polymeric filter layer, the polymer solution comprising a polyamide polymer, a solvent and a free radical source material; Coagulating the polyamide of the polymer solution at the surface; Crosslinking the polyamide 23. A method for preparing a coated filter membrane comprising:

22. 22. The method of claim 21 , wherein the solvent is selected from aliphatic alcohols and chlorinated hydrocarbons.

23. 22. The method of claim 21, wherein the solvent is selected from methanol, ethanol, propanol, butanol, isopropanol, one or more chlorinated hydrocarbons, and combinations thereof.

24. 24. The method of claim 22 or 23, wherein the solvent contains an amount of water.

25. 25. The method of any one of claims 21 to 24, wherein the solvent does not comprise calcium chloride or formic acid.

26. 22. The method of claim 21, wherein the solvent comprises propanol and up to 20 weight percent water based on the total weight of the solvent.

Citation Information

Patent Citations

  • Hydrophilic porous article

    JP1995238181A

  • Reverse osmosis membrane and its surface treating method

    JP1996173777A

  • Composite separation membrane, and separation membrane module using the same

    JP2013166131A

  • Pervaporation membrane and phenol concentration method

    JP2014159023A

  • Composite separation membrane and composite separation membrane element

    JP2017213500A